Cutting performance of diamond coated Si3N4 tool during turning - Souza, J. V C; Nono, M. C A; Machado, J. P B; Silva, O. M M; Melo, F. C L; Ribeiro, M. V. [UNESP] (Trans Tech Publications, 2010)
Silicon nitride cutting tools have been used successfully for machining hard materials, like: cast irons, nickel based alloys, etc. However these cutting tools with diamond coating present little information on dry turning operations of gray cast iron. In the present work, Si3N4 square inserts was developed, characterized and subsequently coated with diamond for dry machining operations on gray cast iron. All experiments were conducted with replica. It was used a 1500, 3000, 4500 m cutting length, feed rate of 0.33 mm/rev and keeping the depth of cut constant and equal to 1 mm. The results show that wear in the tool tips of the Si3N4 inserts, in all cutting conditions, was caused by both mechanical and chemical processes. To understand the tool wear mechanisms, a morphological analysis of the inserts, after experiments, has been performed by SEM and optical microscopy. Diamond coated PVD inserts showed to be capable to reach large cutting lengths when machining gray cast iron. © (2010) Trans Tech Publications.
Keywords: Diamond coating; Gray cast iron; Silicon nitride; Tool wear; Turning; Chemical process; Cutting conditions; Cutting performance; Depth of cut; Dry machining; Dry turning; Feed-rates; Hard material; Morphological analysis; Nickel based alloy; SEM; Tool wear mechanism; Cast iron; Coatings; Cutting tools; Diamonds; Equipment; Machine tools; Machining; Metal working tools; Nickel coatings; Optical microscopy; Silicon; Tribology; Wear of materials; Diamond cutting tools